Glycosidic compounds from Cassia obtusifolia seeds and their inhibitory effects on OATs, OCTs and OATPs. (August 2019) - Wang, Shuangyan; Feng, Keyu; Han, Lifeng; Fang, Xin; Zhang, Youcai; Yu, Heshui; Pang, Xu
Graphical abstract: Three chromone C -glycosides and one new anthraquinone glycoside were obtained from Cassia obtusifolia seeds. Highlights: Three new chromone C -glycosides were obtained from C. obtusifolia for the first time. Inhibitory activities of all isolates against OATs, OCTs and OATPs were evaluated. Constituents of C. obtusifolia and their SLC transporters inhibition were further understand. Abstract: Phytochemical work on water-soluble ingredients extracted from Cassia obtusifolia seeds led to the isolation of twelve glycosidic compounds including three chromone C -glycosides (1 -3 ), two anthraquinone glycosides (4, 5 ), six naphthopyran glycosides (6 -11 ), and one naphthalene glycoside (12 ). The structures of all compounds were identified mainly by spectroscopic data analysis;1 -3 were three new chromone C -glycosides, and4 was a new anthraquinone glycoside. All isolates were evaluated for the inhibitory activities against human organic anion/cation transporters (OATs/OCTs) and organic anion transporting polypeptides (OATPs) The results demonstrated that compound7 exhibited a moderate inhibitory effect on OAT3, while5 showed a moderate effect on OCT1. Compounds4, 6, 8 and10 displayed a moderate inhibitory effect on OATP1B3, and10 inhibits OATP2B1 significantly.